The Inner Circle of Presidents - Arana Araya, Ignacio (Estudios Internacionales, 2023)
Who belongs to the inner circle of presidents remains understudied. Preceding research has mostly focused on advisors and ministers separately, and has not integrated other groups who also influence presidents. I argue that families, advisors, and ministers are members of the inner circle of presidents and support the leaders’ affective, intellectual, and political needs, respectively. I also propose that the inner circle becomes more functional when its three component groups work with a clear division of labor, are diverse, and combine hierarchical and horizontal relations with presidents. Semi-structured interviews conducted with 24 former Latin American presidents support that inner circles are composed of family, advisors, and ministers, although more evidence is needed to assess what constitutes a functional inner circle.